2018
DOI: 10.3892/ol.2018.9127
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab retreatment in patients with metastatic colorectal cancer who exhibited a clinical benefit in response to prior cetuximab: A retrospective study

Abstract: Clinical benefits of cetuximab retreatment in patients with metastatic colorectal (mCRC) have been reported. In the present study, the effect of cetuximab retreatment on predictive markers was investigated by evaluating the clinical benefit of initial cetuximab treatment prior to cetuximab retreatment. Between November 2012 and March 2017, 14 patients with KRAS proto-oncogene GTPase exon 2 wild-type mCRC who exhibited a clinical benefit (confirmed stable disease for at least 6 months or a clinical response) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…These amino acid mutations impair GTPase hydrolase activity and maintain the protein in an activated state, which results in continuous signaling to downstream effectors, even in the absence of extracellular stimulation. In our study, we detected a KRAS mutation rate of 30.9%, which is consistent with previous reports of 30%-40% in China[28] and was lower than those (30%-50%) observed in other countries[27,29-31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These amino acid mutations impair GTPase hydrolase activity and maintain the protein in an activated state, which results in continuous signaling to downstream effectors, even in the absence of extracellular stimulation. In our study, we detected a KRAS mutation rate of 30.9%, which is consistent with previous reports of 30%-40% in China[28] and was lower than those (30%-50%) observed in other countries[27,29-31].…”
Section: Discussionsupporting
confidence: 92%
“…In this manner, the mutant KRAS gene results in a constitutively active GTP-bound state and the activation of downstream pro-proliferative signaling pathways[25,26]. The most common oncogenic mutations in CRCs are point mutations at positions 12, 13, and 61 of KRAS , with approximately 90% being in codons 12 and 13[22-27]. These amino acid mutations impair GTPase hydrolase activity and maintain the protein in an activated state, which results in continuous signaling to downstream effectors, even in the absence of extracellular stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to few efficacious options in later lines of therapy, there has been considerable interest in the possibility of retreating with a systemic therapy used during an earlier line of treatment. Most studies that have reported on this approach have been retrospective, detailing institutional experiences retreating with chemotherapeutics [31][32][33] or targeted therapies (eg, epidermal growth factor receptor [EGFR] inhibitors) 31,[34][35][36][37][38] and concluded that a retreatment approach was feasible, based on response and/or toxicity data. However, these studies were mainly small and did not differentiate between patients who stopped therapy due to progression compared with other reasons, limiting the quality of these data.…”
Section: Therapy Retreatment/rechallengementioning
confidence: 99%
“…Outcomes were better in patients who benefited in the first-line setting with cetuximab, and, notably, in those with a longer interval between the last dose of cetuximab and progression on second-line therapy. 16 18 Moreover, the prospective phase II Cricket trial demonstrated an ORR of 21.5% with cetuximab-based re-challenge treatment, with higher PFS and OS when patients selected by ctDNA analysis did not present RAS mutation in plasma. 19 This, and the previous results, strongly support the value of ctDNA-based selection of patients for the sequential use of cetuximab or panitumumab in refractory patients.…”
Section: Oncogenic Biomarkersmentioning
confidence: 99%